KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SEMESTER GENAP SD NEGERI 1 GULAK GALIK TELUK BETUNG UTARA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Sari, Anita (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
This study discusses the problem of reading comprehension of students of SD Negeri 1 Teluk Betung Galik North Bandar Lampung 2018/2019 academic year. The ability to read comprehension in this study includes: (a) disclosure of the contents of the reading, themes, and facts; (b) the ability to retell; and (c) the ability to draw reading conclusions. This study aims to find out and describe how the level of reading comprehension of students. To achieve the objectives of the study, the authors used a descriptive qualitative method, while the data collection techniques were essay test techniques. The population in this study amounted to 30 students and the study sample was set at 30 people. The sampling technique used is the total sampling technique. Analyzing the data in this study is to use a percentage. Reading comprehension ability in fifth grade students in even semester SD Negeri 1 Teluk Betung Galik North Bandar Lampung 2018/2019 academic year obtained an average score of 69.99 this value is included in the criteria enough. Based on the aspects of the assessment, the value of reading comprehension in the aspects of the disclosure of reading content, themes, and facts is in the sufficient category with an average score of 61.66. The ability to read comprehension in the aspect of retelling ability is in a sufficient category with an average score of 66.66. The ability to read comprehension in the aspect of the ability to draw reading conclusions is in a good category with an average score of 83.33.